Telematics for teacher education: issues from a european conference - Osório, António José (1995)
The world Information Superhighway is under discussion in many countries. Within Europe the discussion is also very active as is the promotion of the use of telematics for trans-European communication and co-operation in various areas. For education and training, representatives of European teacher trainers, teachers, students, parents, policy and decision makers discussed their needs and views on a trans-European network at a conference held in May 1994 in Luxembourg. This paper presents a selection of various issues raised at the conference regarding the use of telematics for teacher education and illustrates the discussion and the method of discussion. It also describes and discusses the conference programme model, as it offered innovative on-line activities to facilitate appreciation of telematics. The case is argued that teacher education can benefit greatly from telematics and some points are put forward for further discussion.